Empresas que Compiten a Través del Trabajo en Equipo - Sáenz Blanco, Fabiola (Ingeniería, 2002)
This articulates is born of an investigation like part of a doctoral thesis that looks for the characteristics of the companies that work in team to settle down. The investigation was made taking like reference mark some companies manufacturers installed in Spain. With base in previous investigations and in the obtained information of the interviews, the experience shared in the companies and the continuous feedback of the same ones through the use of Internet, an analysis of the influence of the decisive factors is made in the implementation of the work in team and the characteristics that determine the work designs implemented in the studied companies settle down